A conceptual model and case study of blockchain-enabled social media platform. (January 2023) - Zhan, Yuanzhu; Xiong, Yu; Xing, Xinjie
Abstract: Nowadays, with the emergence of Web 3.0 and the metaverse, we collectively witnessed the explosive development of the decentralised autonomous organisation and the blockchain business model. Particularly, the advancement of technologies has further given birth to a novel form of social platform as blockchain-enabled social media (i.e., SocialFi), which is growing both in size and number of users. Accordingly, the rapid development of these blockchain-enabled social media firms illustrates the requirement to better understand the reasons behind this increase and the innovative practices and strategies of firms in this emerging field. Using the case of Pixie – the world's first fully functional decentralised photo and video sharing social network based on blockchain technology, this insight paper identifies a conceptual model of blockchain-enabled social media that is useful for illustrating the successful business strategy and operations of firms. Particularly, the identified model employs four pillars of innovation as fundamental technologies, governance and operations, incentive mechanism design, and organisational structure and performance. Based on this crypto economy social media model, the study further presents the main challenges, discusses the implications based on agency theory, as well as highlights several directions for future research associated with blockchain-enabled social media. Highlights: Extends the conceptual basis of decentralised social media. Develops a crypto economy model for blockchain-enabled social media (BSM). Illustrates the successful business strategy and operations of BSM firms. Uses case evidence to support firms developing structures and harvesting values. Highlights the implications of BSM based on agency theory.